Correlation-based feature selection strategy in classification problems - Michalak, Krzysztof; Kwaśnicka, Halina (Zielona Góra: Uniwersytet Zielonogórski)
In classification problems, the issue of high dimensionality, of data is often considered important. To lower data dimensionality, feature selection methods are often employed. To select a set of features that will span a representation space that is as good as possible for the classification task, one must take into consideration possible interdependencies between the features.
Keywords: feature selection; pairwise feature evaluation; feature correlation; pattern classification